Successful transcatheter embolization of an unruptured idiopathic peripheral pulmonary artery aneurysm - Chiaki Sato, MD; Takatoshi Kubo, MD, PhD; Eisuke Shibata, MD, PhD; Masahiro Yanagiya, MD, PhD; Jun Nakajima, MD, PhD; Osamu Abe, MD, PhD (Radiology Case Reports, 2023)
Pulmonary artery aneurysms (PAAs) occurring in the distal branch of the pulmonary artery are rare, and there are only a few reports of transcatheter embolization of unruptured idiopathic peripheral PAAs. We report a case of a 66-year-old woman with a history of surgery for pulmonary arteriovenous malformations who presented with an idiopathic peripheral PAA of A10 confirmed by contrast-enhanced computed tomography and pulmonary artery angiography. Transcatheter embolization was performed to prevent rupture, and the aneurysm was successfully embolized. Although there is no consensus on the indications and treatment for unruptured idiopathic peripheral PAAs, transcatheter embolization may be a favorable treatment option.